A 1:1:1 co-crystal solvate comprising 2,2′-dithiodibenzoic acid, 2-chlorobenzoic acid and N,N-dimethylformamide: crystal structure, Hirshfeld surface analysis and computational study - Tan, Sang Loon *; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The asymmetric unit of the three-component title compound, 2,20 -dithiodibenzoic acid–2-chlorobenzoic acid–N,N-dimethylformamide (1/1/1), C14H10O4S2C7H5ClO2C3H7NO, contains a molecule each of 2,20 -dithiodibenzoic acid (DTBA), 2-chlorobenzoic acid (2CBA) and dimethylformamide (DMF). The DTBA molecule is twisted [the C—S—S—C torsion angle is 88.37 (17)] and each carboxylic group is slightly twisted from the benzene ring to which it is connected [CO2/C6 dihedral angles = 7.6 (3) and 12.5 (3)]. A small twist is evident in the molecule of 2CBA [CO2/C6 dihedral angle = 4.4 (4)]. In the crystal, the three molecules are connected by hydrogen bonds with the two carboxylic acid residues derived from DTBA and 2CBA forming a nonsymmetric eight-membered {HOCO}2 synthon, and the second carboxylic acid of DTBA linked to the DMF molecule via a seven-membered HOCOHCO heterosynthon. The three-molecule aggregates are connected into a supramolecular chain along the a axis via DTBA-C—HO(hydroxyl-2CBA), 2CBA-C—HO(hydroxyl-DTBA) and DTBA-C—HS(DTBA) interactions. Supramolecular layers in the ab plane are formed as the chains are linked via DMF-C—HS(DTBA) contacts, and these interdigitate along the c-axis direction without specific points of contact between them. A Hirshfeld surface analysis points to additional but, weak contacts to stabilize the three-dimensional architecture: DTBA-C OH(phenyl-DTBA), 2CBA-ClH(phenyl-DTBA), as well as a – contact between the delocalized eight-membered {HOC O}2 carboxylic dimer and the phenyl ring of 2CBA. The latter was confirmed by electrostatic potential (ESP) mapping.